Peningkatan Motivasi dan Prestasi Belajar Menulis Teks Eksposisi Menggunakan Model Discokaku Dipadu Gambar Berseri di SMA Negeri 5 Magelang - Eva Ratihwulan; Rangga Asmara (TRANSFORMATIKA, 2019)
This research was aimed to investigate students' motivation and their learning achievement in writing exposition texts. To seek the answer, we used discokaku teaching method and pictorial series. This study was carried out under classroom action research. We implemented three main stages of pre-cycle, cycle I, and cycle II, each cycle using three meetings. The participants were 10th graders of SMA Negeri 5 Magelang. The data were attained from test and non-test techniques. The test technique deployed (1) Kahoot! for assessing their understanding and (2) pictorial series for the writing test. For the non-test, this study adopted some qualitative instruments: journal, observation, interview, and documentation. The result shows that discokaku teaching method and pictorial series were able to improve students’ motivation from 23.47% to 33.87% and their achievement from 3.13% to 78.13% at the end of the cycle 2.